ANALISIS DERAJAT KEUANGAN DAERAH DALAM MENDUKUNG DESENTRALISASI FISKAL DI KOTA KENDARI - Abdullah, Muntu; Intihanah, Intihanah; Albasri, Muhammad Adam (JURNAL AKUNTANSI DAN KEUANGAN, 2017)
This study aims to determine the degree of fiscal decentralization fiscal decentralization support able kendari period 2010-2014. Fiscal ability already kendari city meets the needs fiscal period 2010-2014. This type of study using is a quqntitative study using secondary data. Descriptive data analiysis method to define the degree of fiscal decentralization, needs fiscal, fiscal capacity, independence.The results showed thet the degree of fiscal decentralization in kendari city in the 2010-2014 period is still relatively less, with the percentage of 13,38% and fiscal need to be relatively les. This shows the lower the fiscal needa of a region can be said that the more efficientÂ  financing Fiscal decentralization degree fiscal support is still lacking, this can be proved by the degree of fiscal decentralization kendari city with an averge of 13,38% so classified is still lacking. Fiscal need kendari city has an averge index of 12.02 service then this shows that financing is still relative lacking.